Management of Infrastructure in Improving the Quality of Vocational High School Graduates - Aisah, Iis; Achmad, Achmadi; Khoeriah, N. Dede; Sudrajat, Adjat (Journal of Industrial Engineering & Management Research, 2021)
The dissertation with the title "Management of Infrastructure in Improving the Quality of Vocational High School Graduates" focuses on case studies conducted by Vocational School in an effort to improve the quality of Vocational High School graduates. So far the management of facilities and learning infrastructure that standardized Laboratory of Honda motorcycle business techniques with disadvantages is less running to the maximum that causes the absorption of graduates to the Dudi still low. While the demands of real needs are increasing competitiveness through the quality of graduates who are ready to work, where the output and outcome graduates are priority. The general purpose of this study is to determine and analyze the Management of Facilities and Infrastructure in Improving the Quality of Vocational High School Graduates. The specific objectives to be achieved at the end of this research are: (1). Knowing and explaining the facilities and infrastructure management program in improving the quality of Vocational High School graduates; (2). Implementation of facilities and infrastructure management in improving the quality of Vocational High School graduates; (3). Problems faced in implementing the management of facilities and infrastructure in improving the quality of Vocational High School graduates; (4). Future demands related to the management of facilities and infrastructure in improving the quality of Vocational High School graduates; (5). Future improvement steps in the management of facilities and infrastructure in improving the quality of Vocational High School graduates. In order to get a comprehensive picture of this, research was conducted with a case study approach at Vocational High School Lentera Bangsa 1 Karawang, Vocational High School Lentera Bangsa 2 Karawang and Vocational High School Rismatek Karawang with qualitative methods. Based on the interpretation and analysis of the research results, the general conclusion is that the facilities and infrastructure management program has improved the quality of graduates which has an impact on the quality of graduates who are absorbed in the world of work, including: (1). Facilities and infrastructure management program in improving the quality of Vocational High School graduates who have the knowledge, skills and work ethic in accordance with the demands of the job market; (2). Implementation of management of facilities and infrastructure together carry out learning and assessment together in educating, training and providing qualified and work-ready workforce; (3). Problems encountered related to disproportionate number of industries and lack of practical equipment; (4). Future demands related to collective agreements in producing vocational graduates who are ready to work and competitive according to the demands of DUDI; (5). The next improvement step is to open foreign investment as a step to increase DUDI and complete school facilities and infrastructure.